Farewell formula as an element of the textual framework in Polish epistolography of the 17th and 18th centuries - Sicińska, Katarzyna (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The subject of the article is the farewell formula present in Polish epistolography of the 17th and 18th centuries. It is an important element in the structure of a letter and a determinant of its genre. The formula has primarily a phatic and pragmatic function, that is, it extinguishes and ends the contact between the partners in an epistolary dialogue while maintaining an atmosphere of politeness. In addition, it has a delimiting function, that is it sets the boundaries of the epistolary text and ensures its coherence. The farewell formula may be a statement of the end of the epistolary dialogue e.g. with these words I conclude (tymi słowy kończę), or it may signal an indirect intention to end the dialogue — by indicating the exhaustion of the topic e.g. I have nothing more to report; I have nothing more to announce (więcej nie mam co donieść; więcej nie mam nic do oznajmienia) or the necessity to abandon contact for the sake of the addressee e.g. I do not want to bother you reading my words, I do not tell old chestnuts (nie bawię pisaniem, nie zatrudniam ramotą).